Task-shifting: experiences and opinions of health workers in Mozambique and Zambia - Ferrinho, Paulo (BioMed Central, 2012)
BACKGROUND: This paper describes the task-shifting taking place in health centres and district hospitals in Mozambique and Zambia. The objectives of this study were to identify the perceived causes and factors facilitating or impeding task-shifting, and to determine both the positive and negative consequences of task-shifting for the service users, for the services and for health workers. METHODS: Data collection involved individual and group interviews and focus group discussions with health workers from the civil service. RESULTS: In both the Republic of Mozambique and the Republic of Zambia, health workers have to practice beyond the traditional scope of their professional practice to cope with their daily tasks. They do so to ensure that their patients receive the level of care that they, the health workers, deem due to them, even in the absence of written instructions. The “out of professional scope” activities consume a significant amount of working time. On occasions, health workers are given on-the-job training to assume new roles, but job titles and rewards do not change, and career progression is unheard of. Ancillary staff and nurses are the two cadres assuming a greater diversity of functions as a result of improvised task-shifting. CONCLUSIONS: Our observations show that the consequences of staff deficits and poor conditions of work include heavier workloads for those on duty, the closure of some services, the inability to release staff for continuing education, loss of quality, conflicts with patients, risks for patients, unsatisfied staff (with the exception of ancillary staff) and hazards for health workers and managers. Task-shifting is openly acknowledged and widespread, informal and carries risks for patients, staff and management.